Variables Study Cause Of Delivery Of The Boyolali Road Improvement - Jrakah / Selo On 2015 - Helmy Five Arifianto; Soedarsono Soedarsono; Djoko Susilo Adhy (International Conference on Coastal and Delta Areas, 2017)
Various physical infrastructure activities carried out to improve road performance one of them with improvement and improvement of roads. Package of road improvement activities Boyolali - Jrakah / Selo is worth 19.5 billion more with the type of handling of concrete road pavement + concrete widening + 2 layer overlay over 4 km. However, the timing of the activities specified during the 240 working days is delayed due to various factors. Though this road has a function and a very important role that disrupt the activities of society and the flow of agricultural goods. The purpose of this study is to determine the factors causing the delay of the project Improving the Road of Boyolali - Jrakah / Selo in 2015. The research method used is descriptive approach method. The survey method was conducted to capture the opinions, experiences and attitudes of the respondents on the issues in road improvement project of Boyolali-Jrakah / Selo road in Boyolali Regency through questionnaire and institutional survey. The sample of research using all members of the population is called total sample or census which amounts to 60 respondents. The analysis technique used is factor analysis. While the variables used are labor, materials, equipment, design, planning and implementation, financing, social environment and community and managerial. Keywords: project delays, road improvements, Boyolali-Jrakah road